Evaluation of Psychological Distress in Infertile Women who Underwent ART Cycle During the COVID-19 Pandemic - Ebru Cogendez; Pinar Kumru; Sunullah Soysal; Enis Ozkaya; Belgin Devranoglu; Elif Tozkir; Ilhan Sanverdi (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: We aimed to determine the frequency of psychological distress and related factors in infertile women who underwent assisted reproductive technologies during the COVID-19 pandemic and to develop health policies accordingly.